Biological wastewater treatment - Grady, C. P. Leslie, Jr.; Daigger, Glen T. ;Love, Nancy G.;Filipe, Carlos D. M. (Boca Raton, Florida : CRC Press, 2011)
Written by experts in the field, this thoroughly updated third edition covers commonly used and emerging suspended and attached growth reactors. Drawing on their extensive academic and industrial experience, the authors discuss combined carbon and ammonia oxidation, activated sludge, biological nutrient removal, aerobic digestion, anaerobic process.
pt I. Introduction and Background -- pt. II. Theory: Modeling of ideal suspended growth reactors -- pt. III. Applications: Suspended growth reactors -- pt. IV. Theory: Modeling of ideal attached growth reactors -- pt. V. Applications: Attached growth reactors -- pt. VI. Future challenges.
Includes bibliographical references and index.
Keywords: SEWAGE -- PURIFICATION -- BIOLOGICAL TREATMENT